Design, synthesis, and biological activity of novel halogenated sulfite compounds - Yingshuai Liu; Guozhu Sheng; Baohong Liu; Ruofei Yin; Yaoyao Du; Bin Li (PLoS ONE, 2025)
The acaricide propargite has been widely used for over 50 years without significant resistance issues. Addressing to the propargite defects of poor crop safety, thirty-six novel halogenated propargite analogues were designed, synthesized, and characterized using 1H NMR, 13C NMR spectroscopy, and HRMS. All target compounds were screened for activity against adult Tetranychus cinnabarinus (spider mites) and Myzus persicae (aphids). Two compounds exhibiting higher insecticidal activity were further evaluated for crop safety on cowpea seedlings. Structural modifications, such as replacing the tert-butyl group on the propargite benzene ring with chlorine or trifluoromethoxy, and substituting the propargyl group with fluorinated alkyl groups (e.g., 2-fluoroethyl or 3,3,3-trifluoropropyl), significantly enhanced both acaricidal and aphicidal activity. Compound 5.16 demonstrated superior acaricidal activity (LC50: 14.85 mg L-1) on Tetranychus cinnabarinus and excellent crop safety on cowpea seedlings. Additionally, Compound 5.32 exhibited both acaricidal (LC50: 14.32 mg L-1) and aphicidal activity, which is unusual in this chemical class. The compounds 5.16 and 5.32 could be used as promising leads for the discovery of novel acaricides or insecticides.